Internet server construction kit for windows - Bean, Greg (New York: John Wiley & Sons, 1995)
The Book All about Windows WWW, Gopher, FTP, WAIS, Finger, and Mail servers and how to choose the one that's best for you Step-by-step directions on how to install, configure, and troubleshoot Internet server software in the Windows 3.1, Windows 95, or Windows NT environments Guidelines on how to design customized home pages using HTML Expert tips on maintaining security and conducting safe cash transactions over the Internet And much more The CD WinSock--a TCP/IP protocol that lets Windows work on the Internet WWW HTTP--a Web server for Windows that lets you create your own home page and lets Mosaic users access your information HGopher--lets Gopher users access your information Sample home pages and templates Configuration files for all the included software to make installation easier Sample code for utility programs that add high functionality to your WWW server You like the idea of having an Internet server of your own, but you're intimidated by the time, cost, and sheer technical difficulty involved. Don't be. Let expert Greg Bean show you just how quick and easy it can be to establish an Internet presence on par with the big guys, but at a fraction of the cost! Whether you are a small publisher, business consultant, nonprofit organization, or fan club...no matter what your product, service, or special interest, this book/CD set supplies you with all the tools and expert guidance you need to become a part of the Internet, create your own unique look, and maintain total control over your service.
Building Internet Servers. Internet Standards and Protocols. Server Application: Background and Concepts. FTP Servers. Gopher Servers. World Wide Web Servers. HTML Authoring and Editing. Web Utilities. Finger Servers. Mail Servers. Wide Area Information Servers(WAIS). Appendix. Glossary
Includes index.
Keywords: Internet (Computer network).